Assessment of Factors Causing Lack of Interest among Small-Scale Farmers in Agriculture System in Tehsil Shakargarh, Pakistan - Haider, Samsam; Ashraf, Ejaz; Javed, Muhammad Arshad (PSM Biological Research, 2016)
This study aimed to highlight the factors that enforce the small-scale farmers to take the least interest in agricultural activities. The study showed the destructive effects of factors like socio-economic, techno-economic, Government policies, Natural disasters and all those factors that are major obstacles in minimizing their low production. The data was collected from 110 respondents from Tehsil Shakargarh by using multi-stage random sampling technique. Statistical Package for Social Sciences (SPSS) was used to interpret the data. The study showed that neither Small-scale farmers in Tehsil Shakargarh are ready to take care of their full monetary expenses nor to create their income because of low cash costs. Their output is much less than from their investment, which took away the entire livelihood from them and made them more vulnerable. The study also put some light on extension department role in creating awareness among small farmers. Proper steps should be taken to narrow these problems.